2016
DOI: 10.3109/17435390.2015.1132343
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and intracellular dissolution of nickel nanowires

Abstract: The assessment of cytotoxicity of nanostructures is a fundamental step for their development as biomedical tools. As widely used nanostructures, nickel nanowires (Ni NWs) seem promising candidates for such applications. In this work, Ni NWs were synthesized and then characterized using vibrating sample magnetometry, energy dispersive X-Ray analysis and electron microscopy. After exposure to the NWs, cytotoxicity was evaluated in terms of cell viability, cell membrane damage and induced apoptosis/necrosis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 38 publications
5
55
1
Order By: Relevance
“…The results showed that Ni NWs are quickly internalized (within less than 1 hour) by cultured colon cancer cells and do not cause extensive cytotoxicity at a concentration of 2.4 μg/mL and an incubation time of 1 hour, which confirms previous results obtained for incubation times up to 72 hours. 33 The highest and significant viability drop of 11% was found for a higher NW concentration (12 μg/mL) and 1 hour incubation.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The results showed that Ni NWs are quickly internalized (within less than 1 hour) by cultured colon cancer cells and do not cause extensive cytotoxicity at a concentration of 2.4 μg/mL and an incubation time of 1 hour, which confirms previous results obtained for incubation times up to 72 hours. 33 The highest and significant viability drop of 11% was found for a higher NW concentration (12 μg/mL) and 1 hour incubation.…”
Section: Resultsmentioning
confidence: 98%
“…The cytotoxic effects might increase with longer incubation times, as has been shown before. 33,36 This would have to be taken into account in in vivo applications. For instance, it has been shown that iron oxide nanoparticles remain in an organism for several days 56 or even up to 6 months.…”
Section: Magnetic Nws-cells Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Phagocytic cells can actively engulf magnetic nanowires, as has been recently demonstrated in elegant experiments using selective chemical inhibitors of different internalization pathways. 39 …”
Section: Discussionmentioning
confidence: 99%